Internalisasi Nilai Fiqih Bi’ah dalam Membentuk Karakter Green Generation di Sekolah Adiwiyata - Risa Marjanah; Marhamah Saleh (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the process of internalizing fiqih bi’ah values and its contribution to shaping the green generation character in Adiwiyata schools. The background of the research is based on the low awareness of students regarding environmentally friendly behavior. The approach used is qualitative with a descriptive method. Data were collected through interviews, observation, and documentation involving Islamic Religious Education teachers, Adiwiyata Coordinators, and Adiwiyata cadres. The results of the study show that the internalization of fiqih bi’ah values is carried out through three main strategies, namely the delivery of values, habituation and practice, and reinforcement of values. The delivery of values is carried out through the integration of the learning curriculum, especially in Islamic Religious Education subjects. Habituation is realized through school Adiwiyata program activities. Value reinforcement is applied through the exemplary behavior demonstrated by all school members in daily activities. This process shapes students' character, which includes care and responsibility, discipline, living a clean and healthy life, as well as environmental awareness. These findings indicate that a religious value-based approach reinforces the implementation of Adiwiyata schools in forming the character of the green generation sustainably. The results of this study can serve as a reference for Islamic schools and education policymakers in integrating religious values into environmental education programs to shape a generation that is caring and responsible for environmental sustainability.